Flexural characterization of polymer concrete comprising waste marble and date palm fibers - Rokbi, Mansour; Rahmouni, Zine El Abidine; Baali, Brahim (Technical Sciences, 2019)
Three-point bending. Abstract This work is an experimental approach for the development and characterization of a polymer concrete reinforced with natural fibers. The polymer concrete consists of sand (Quartz) and orthophthalic polyester used as a binder. Marble powder was used to ensure the continuity of the particle size of the granular mixture. As reinforcement, 2% of chopped date palm fibers (short, very short or mixed) were added. For comparison, identical polymer concrete flexure specimens reinforced with the same content of short E-glass fibers were also prepared and tested. All specimens were initially cured at room temperature and then post-cured for 6 h at 70°C. The results of three-point bending on smooth specimens with different rates of charges (marble), showed that the flexural and compressive strength were improved by adding 20% of marble, and were 31.80 MPa and 67.42 MPa respectively. The flexural strength of specimens showed that the improvement or the degradation of polymer concrete properties seemed to be attributed to the nature of fibers (treated or untreated), and/or to the fibers sizing (short, very short or mixed).